Jurnal Akuntansi & Investasi: Pengaruh Kas, Bonus SWBI (Sertifikat Wadiah BI), Marjin Keuntungan, n Dana Pihak Ke 3 terhadap Pembiayaan Murabahah (Studi Empiris Pada Bank Umum Syariah di Indonesia - Kristia Octaviana, Emile Satia Darma (Akuntansi FE UMY, 2012)
The paper tries to the factors which bring influence toward murabahah financing. Methods used in this research is to use Linear Regression models with SPSS software in statistical time series (time series) from January 2008-December 2010 on Sharia Public Banks. From the analysis conducted by the preparation is obtained that the independent variable (cash, SWBI bonus, profit margin, and third party fund) jointly was able to influence the dependent variable that is murabahah financing.